Beauty Representation (Semiotic Analysis of Roland Barthes in Rachel Goddard Youtube Account) - Afrilia Wening Anindya; Dr. Lintang Ratri Rahmiaji, M.Si (Interaksi Online, 2017)
This research was started from beautiful meaning that remains a problem for women and still debated to this day. Rapid technological development, until the advent of vlog makes the concept of beauty changes. One of vlogger that discusses about beauty on her YouTube account is Rachel Goddard. She presents vlog about makeup tutorials, tips on caring for the body and face, also reviews on beauty products through her youtube account. The aim of this research is to know the beauty representation based on Semiotic analysis and also to dismantle the myth of what was built by Rachel Goddard. In analyzing vlog about beauty tutorials titled "Learning Makeup For Beginners" in the Rachel Goddard YouTube account, the writer using semiotic researchers from Roland Barthes. The first conclusion of this research is beauty representation still refer to the same criteria, but with the development of technology, beauty criteria has expanded. Beauty criteria that have expanded is thick and tidy eyebrows; big and colorful eyelids; curly, thick, and long eyelashes; eyes that look big; under eye that look bright; flawless, smooth, and perfect face; rosy cheeks; and colored lip in order not to look pale. The second conclusion of this research is beauty criteria still oriented to the western culture. This is evidenced by the figure of Rachel Goddard who became a model in the vlog also many makeup products and foreign language vocabulary that she used.